MANAGING CONSTRUCTION PROJECTS IN A MULTICULTURAL SOCIETY: PERSPECTIVE OF FILIPINO CANADIAN ENGINEERS - Dave Estrella; Ericson Z. Matias; Jay A. Sario (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This research study was intended to examine the effect of national culture and leadership styles of Filipino- Canadian Engineers based on Hofstede’s cultural dimensions. The purpose of this academic research is to find a leadership program that will bridge the gap of underrepresentation among the Filipino Canadian Engineers and Project Managers in Canada. The respondents of this research study are the internationally trained Filipino Engineers who are members of the Association of Filipino Canadian Engineers (AFCE). This researcher used a combination of self- made and standardized Survey Questionnaires published on Google Forms, as well as face to face interviews where permitted. The questionnaires were sent via email or social media platforms such as Messenger and LinkedIn. The data collected were then tallied, analyzed, interpreted and summarized using statistical treatment such as Mean, Pearson r correlation, Standard Deviation and Frequency. The study revealed that Filipinos has assimilated well to the Canadian Society in terms of cultural dimensions with the exemption of Collectivism. This research study also found out that there are leadership traits or skills that need to be tweaked in order for the Filipino Canadian Engineers to be a productive part of Engineering and Construction industry. This researcher identified workshops including Assertiveness training, Critical and creative thinking, Emotional Intelligence, Intercultural and interpersonal communication, and public speaking shall be introduced.